Case report: Successful therapy with azacitidine for acute myeloid leukemia with NUP98::RARG resembling acute promyelocytic leukemia - Wei, Zhichen; Shao, Linlin; Xu, Shuqian; Zhang, Xiaolin; Wang, Lin; Qin, Ping; Song, Qiang; Hou, Ming (Frontiers in Oncology, 2024)
We report a case of acute myeloid leukemia (AML) with retinoic acid receptor gamma (RARG) rearrangement, exhibiting clinical, morphological, and immunophenotypic features similar to classic acute promyelocytic leukemia (APL). RNA sequencing analysis of the patient’s bone marrow samples revealed the presence of nucleoporin 98 (NUP98)-RARG caused by translocation. AML with RARG rearrangement is insensitive to all-trans retinoic acid (ATRA) and arsenic trioxide. The patient received azacitidine therapy after failing ATRA and standard 3 + 7 therapy (idarubicin and cytarabine) and achieved complete remission. Conclusively, this acute myeloid leukemia subtype may benefit from azacitidine.